CAN THE REPUTATION OF PUBLIC ACCOUNTANTS MODERATE AUDIT DELAY? - Enung Nurhayati; Amir Hamzah; Vikka Nurmunasyaroh (Universitas Pakuan, 2023)
ABSTRACTThe aim of this study is to investigate and analyze empirical facts related to the factors that influence audit delay, with KAP’s reputation serving as a moderating variable. The research methods employed in this study were descriptive and affirmative, with the population consisting of 245 financial statements from 49 mining manufacturing companies listed on the Indonesia Stock Exchange. A sample of 31 businesses was selected, and logistic regression was used for analysis. The findings of this study indicate that KAP’s reputation has both positive and negative effects on audit delay. This suggests that audit delay profitability can be moderated by KAP’s reputation. Additionally, the study revealed that dissolvability affects review delay, Organization size affects review deferral, and Benefit significantly affects review delay. KAP’s reputation can moderate the effect of solvency on audit delay, strengthening or reducing the relationship between audit delay and solvency. KAP’s reputation can also moderate the impact of company size on audit delay by strengthening or moderating the relationship between audit delay and company size. It is crucial to maintain a good reputation to mitigate the negative impact of audit delay that can help build trust with clients and increase the demand for their services.ABSTRAKThis study aims to analyze empirical facts related to the factors that influence audit delay, with KAP's reputation as a moderating variable. The research method used is descriptive and affirmative, with a population consisting of 245 financial reports from 49 mining manufacturing companies listed on the Indonesia Stock Exchange. The selected sample is 31 companies. The analytical method uses logistic regression. The results of this study indicate that profitability, solvency, firm size have an effect on audit delay. In addition, KAP's reputation can moderate the influence of solvency on audit delay, strengthening or reducing the relationship between audit delay and solvency. KAP reputation can also moderate the impact of company size on audit delay by strengthening or moderating the relationship between audit delay and company size. This shows that it is important to maintain a good KAP reputation to reduce the negative impact of delayed audits which can help build trust with clients and so on, increase the demand for their services.